2023
DOI: 10.1155/2023/6694536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bio-Slurry and Chemical Fertilizer Application on Soil Properties and Food Safety of Tomato (Solanum lycopersicum Mill.)

Abstract: This study evaluated the effects of bio-slurry (BS) and chemical fertilizer (CF) application on soil properties and food safety of tomato (Solanum lycopersicum Mill.). A field experiment consisting of 100% BS (5 ton BS ha−1), 100% CF (90 kg N·ha−1 + 30 kg P·ha−1 + 13 kg S·ha−1), and control was conducted. Soil samples from all the treatments were collected for their physico-chemical characteristics. The level of ten heavy metals in experimental soil and tomato fruit samples was also determined. Compared to CF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Collectively, the integrated application of chemical fertilizer and bio-slurry increased height over their separate application. Findings from previous studies indicated that the use of chemical fertilizer and bio-slurry gives premier height over the control in lettuce [ 16 , 17 ], in tomato [ 14 ] and okra [ 18 ]. This might attribute to the high nutrient and organic matter contents of bio-slurry, which optimize both the deficit and the excess nutrients in the soil [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Collectively, the integrated application of chemical fertilizer and bio-slurry increased height over their separate application. Findings from previous studies indicated that the use of chemical fertilizer and bio-slurry gives premier height over the control in lettuce [ 16 , 17 ], in tomato [ 14 ] and okra [ 18 ]. This might attribute to the high nutrient and organic matter contents of bio-slurry, which optimize both the deficit and the excess nutrients in the soil [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the application of chemical fertilizer and bio-slurry, as sole or integration, increased both growth and yield of lettuce. A prior study found that when chemical fertilizer and bio-slurry were applied together, there was a significant positive correlation between the overall fruit yield and yield components in tomatoes [ 14 ] and in maize [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation